Ramona and Beezus [videorecording (DVD)] - Rosenbaum, Elizabeth Allen; Moynahan, Bridget, 1972-; Goodwin, Ginnifer; Duhamel, Josh, 1972-; Oh, Sandra, 1971-; Corbett, John, 1961-; Gomez, Selena, 1992-; Cleary, Beverly (Twentieth Century Fox Home Entertainment, 2010)
Ramona is a little girl with a very big imagination and a nose for mischief. Her playful antics keep everyone in her loving family on their toes, including her older sister Beezus, who's just trying to survive her first year of high school. Through all the ups and downs of childhood, Ramona and Beezus learn that anything's possible when you believe in yourself and rely on each other. Based on the best-selling books by Beverly Cleary.